COPII proteins exhibit distinct subdomains within each ER exit site for executing their functions - Maeda, Miharu (Sci Rep, 2019)
Secretory proteins are exported from special domains of the endoplasmic reticulum (ER) termed ER exit sites, via COPII-coated carriers. We recently showed that TANGO1 and Sec16 cooperatively organize mammalian ER exit sites for efficient secretion. However, the detailed spatial organization of mammalian ER exit sites is yet to be revealed. Here, we used super-resolution confocal live imaging microscopy (SCLIM) to investigate the localization of endogenous proteins, and we identified domains abundant in transmembrane complexes (TANGO1/cTAGE5/Sec12) juxtaposed to Sec16. Interestingly, this domain can be distinguished from the inner and the outer coats of COPII proteins within each mammalian ER exit site. Cargoes are partially concentrated in the domain for secretion. Our results suggest that mammalian ER exit sites compartmentalize proteins according to their function in COPII vesicle formation.